Pelatihan Penggunaan Instrumentasi Non-Tes bagi Guru Bimbingan dan Konseling di SMA Negeri 5 Kendari - Minarti Usman; Wa Ode Saktila Mayang Sari; Fitrianingsih; M. Ridwan Tahir; Arni Nur Laili; Muhammad Fadillah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service program aims to enhance the competencies of Guidance and Counseling teachers in using non-test instruments to comprehensively analyze students’ needs. Based on preliminary observations at SMA Negeri 5 Kendari, it was found that most Guidance and Counseling teachers had not yet fully mastered how to design, utilize, and interpret non-test instruments such as problem checklists, needs assessment questionnaires, interviews, and observations. In fact, these instruments are essential for supporting the development of targeted and effective guidance and counseling programs. This community engagement activity was conducted through an intensive six-week training program involving lectures, discussions, and practical simulations. Evaluation results showed an improvement in participants’ knowledge and skills in using non-test instruments, as evidenced by their active involvement, understanding of the material, and success in producing student needs analysis worksheets. This initiative not only provides practical benefits for BK teachers in carrying out their professional duties, but also represents a concrete contribution by academics in bridging the gap between educational theory and practice in schools.